Modeling the drug release from reduced graphene oxide-reinforced hyaluronic acid/gelatin/poly(ethylene oxide) polymeric films - KÜÇÜKADA, KURTUL; ALEMDAR YAYLA, NESLİHAN (ELSEVIER SCI LTD, 2019)
Herein, electroconductive polymeric films consisting of hyaluronic acid (HyA), gelatin (Gel), poly(ethylene oxide) (PEO) reinforced by reduced graphene oxide (RGO) were used in drug release studies to investigate usability of the films as drug carrier in the future. Irbesartan (IRB) used for the treatment of cardiovascular diseases was loaded to the polymeric films and its release kinetic was investigated. Afterwards, the obtained controlled drug release data were simulated using different dynamic differential mathematical models such as 1st, 2nd, 3rd degree and Higuchi model. In addition, a novel approach considering the drug release rate to be inversely proportional to the drug release percentage was presented to reproduce the experimental drug release percentage results. Thus, the approach used in this work covers different aspects of drug release kinetics to assure that HyA/Gel/PEO films w/out RGO could be considered as a potential carrier for controlled drug delivery systems.
Keywords: Hyaluronic acid; Gelatin; Reduced graphene oxide; Drug release rate models; Numerical differentiation; HYBRID SCAFFOLDS; DELIVERY; FABRICATION; MICROSPHERES; BIOMATERIALS; MANAGEMENT; IRBESARTAN